2021
DOI: 10.1177/1010539520983671
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Sociodemographic, Macroeconomic, and Health Resources Factors on Life Expectancy

Abstract: Objective This review was aimed at systematically synthesizing and appraising the existing literature of sociodemographic, macroeconomic, and health resources factors on life expectancy. Methods A systematic literature search of English databases, that is, PubMed/MEDLINE were scrutinized for exploring sociodemographic, macroeconomic, and health resources factors on life expectancy. The literature search was conducted in January 2020, covering a total of 46 articles from 2004 to 2019 met the review criteria, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 52 publications
0
23
0
1
Order By: Relevance
“…From the macroeconomic perspective, most literature proved that there is always a strong relationship between the economy and LE 7,73 . In this model, GDP can show the value of the national output in a period and may grow or rebound quickly during a socioeconomic downturn.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…From the macroeconomic perspective, most literature proved that there is always a strong relationship between the economy and LE 7,73 . In this model, GDP can show the value of the national output in a period and may grow or rebound quickly during a socioeconomic downturn.…”
Section: Discussionmentioning
confidence: 99%
“…9,14 In short, health expenditures are always thought to have a direct impact on LE, and several studies have confirmed this relationship; however, a recent systematic review found that macroeconomic (ME) indicators such as GDP, Gini index, inflation rate, and petroleum/fossil fuel export/consumption were almost equally important, along with health care expenditures. 7…”
Section: Impacts Of Macroeconomic Factors On Life Expectancy In Bahrainmentioning
confidence: 99%
See 3 more Smart Citations